Constructions in Minimalism: A Functional Perspective on Cyclicity - Trotzke, Andreas (Frontiers in Psychology, 2020)
This paper presents a minimalist perspective on syntactic cyclicity that is compatible with fundamental ideas in construction-grammar approaches. In particular, I outline an approach to syntactic structure building where units of potentially any phrasal size can be atomic items in the syntactic derivation, showing that the opposition between words and phrases in minimalism is as artificial as in many construction-grammar approaches. Based on this new perspective on structure building, I focus on the empirical domain of subextraction patterns out of complex subjects, adjuncts, and complements, and I demonstrate that the acceptability patterns in this domain can be explained by a functional approach to syntactic cyclicity: Unacceptable patterns are ruled out not for configurational (and hence syntactic) reasons, but rather they systematically follow from infelicitous interpretations at the syntax-discourse interface. This raises the question of whether syntactic cyclicity is (at least in part) motivated by performance constraints, which I consider another area for fruitful interaction between construction-grammar and usage-based accounts on the one hand and minimalism on the other hand.